Internal Communication Obstacles in The Implementation of Employee Value Proposition: Viewed from State-Owned Company - Lina Setiawati (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
Dealing with the uncertainty in business conditions, several companies are missing out the opportunity to increase employee engagement and attract while also sustaining top talent. Because employees today have increased bargaining power, the job market is highly transparent, and attracting top skilled workers is a highly competitive activity. Hence, today more companies should be taken seriously to developing the analytic solutions related on retaining the employee within the organizations. This paper analyses interaction between employees through internal communication, which involves Employee Value Proposition (EVP) program in one of the state owned company in Indonesia. The analysis shows that in such cases, there is a need to collaborate between employee and employer to choose suitable communication model in attract and retain talent. In this research focus to develop analytical approach to analyse communication of EVP in order to choose the suitable internal communication model for one of state-owned company in Indonesia. This study was supposed to start with qualitative, processed by quantitative and end with qualitative data analysis methods. The study finds employee unsatisfied with the amount/number and quality of information that employees get. To overcome that, company advised to create a new channels communication for all of the employees to share information either internal news or public news.